Housing affordability index for districts in Perak - Mohamed Osman, Mariana; Muhamad Yusup, Siti Wahidah; Abdullah, Muhammad Faris; Shuid, Syafiee (American Scientific Publishers, 2017)
Housing Affordability is one of the major concerns for the State Government of Perak. Affordable housing is important as it has become an absolute necessity of residents, especially for B40 income households’ population in Perak. In Perak, the soaring house prices have made it almost impossible for the middle-income group to afford a home. The drastic changes in housing prices has affected the affordability levels in Perak. This study compares household income against housing prices in each district in Perak. The data were collected from secondary sources and content analysis were undertaken to identify housing affordability in Perak. Housing Affordability Index was subsequently generated. Based on the Index, it is found that housing affordability for each district in Perak at severely unaffordable level. The findings of this study can be used to aid the state government in their endeavours to provide quality affordable housing for Perakian.